Revamping E-Commerce Affiliate Contracts to Address Payment Delays Effectively: Pembenahan Kontrak Afiliasi E-Commerce untuk Mengatasi Penundaan Pembayaran Secara Efektif - Pitaloka, Vernanda Diah; Mediawati, Noor Fatimah (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract: This study investigates the legal dynamics surrounding electronic contracts between TikTok and its affiliates, particularly focusing on commission payment delays before and after TikTok's sale and purchase agreement with Tokopedia. The general background highlights the growing importance of affiliate marketing in e-commerce and the need for clear contractual obligations. The specific background identifies recurring issues related to late commission payments in TikTok’s affiliate agreements, underscoring a significant gap in the legal framework governing these contracts. The primary aim of this research is to analyze changes to TikTok's affiliate agreement post-transaction with Tokopedia, employing normative research methods with a statutory and conceptual approach. The results indicate that the updated TikTok Shop affiliate agreement offers enhanced legal protection, allowing affiliates to file lawsuits in case of violations, and outlines alternative dispute resolution mechanisms, such as complaints at the Seller Center and customer support. The novelty of this study lies in its comprehensive analysis of the amendments to the affiliate agreement, including stricter payment schedules and improved reporting procedures, addressing previous inconsistencies. The implications suggest that these enhancements contribute to better legal protection for affiliates and foster transparency in payment processes, which is crucial for affiliate trust and the overall efficacy of e-commerce operations in Indonesia. Highlights: Legal Dynamics: Explores TikTok's affiliate contracts and commission payment challenges. Updated Agreement: Highlights improvements post-Tokopedia sale for timely commission payments. Dispute Resolution: Discusses mechanisms for addressing payment delays and ensuring clarity. Keywords: TikTok, Tokopedia, affiliate agreements, electronic contracts, commission payments